Prototype of electrical generator development based on water flow pressure - Sahazati Md Rozali; Rozilawati Mohd Nor; Norfariza Ab Wahab; Aliza Che Amran; Saleha Mohamad Saleh; Muhammad Nizam Kamarudin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
Electric potential energy or kinetic energy produces electrical energy. The integration of electrical current and potential yields the energy that is deliverable to the end user via electrical circuitries. There are various techniques used to produce electric energy. Typically, electricity is generated by using fossil fuels or natural gas. However, these resources are facing the extinction problem. Thus, another established method to generate electricity is by using water flow pressure in hydroelectric station. This work presents a model of small electrical generator developed based on the theory of pressure yielded by water stream. The development of conventional hydroelectric generator station destroyed the nature environment and caused the death of animal, especially in the water. Therefore, a turbine in a spherical shape that is integrated with microcontroller is suggested in this work with external passage that is attached to the turbine to reduce the catastrophic effect to the aquamarine and nature. The analysis is conducted on the different material while designing the basin, size of basin radius and the structure of model outlet inlet. The results show that the turbine that is designed by using polyvinyl chloride (PVC) with 10 cm radius produced higher voltage at 5.8 V compared to the other types of basin material and radius